Exploring mosquito virome dynamics within São Paulo Zoo: insights into mosquito-virus-environment interactions - Guimarães, Lilian de Oliveira; Ribeiro, Geovani de Oliveira; da Couto, Roseane; Ramos, Endrya do Socorro Foro; Morais, Vanessa dos Santos; Telles-de-Deus, Juliana; Helfstein, Vanessa Christe; Santos, Jesus Maia dos; Deng, Xutao; Delwart, Eric; Pandey, Ramendra Pati; de Camargo-Neves, Vera Lucia Fonseca; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundMosquito-borne diseases have a significant public health threat worldwide, with arboviruses accounting for a high proportion of infectious diseases and mortality annually. Brazil, in particular, has been suffering outbreaks of diseases transmitted by mosquito viruses, notably those of the Aedes genus, such as dengue, Zika, and chikungunya. Against this background, the São Paulo Zoo is an intriguing ecological niche to explore the virome of mosquitoes, potentially shedding light on the dynamics of arbovirus transmission within a confined setting.MethodsIn this study, we conducted a comprehensive metagenomic analysis of mosquitoes collected from diverse habitats within the zoo, focusing on the Aedes, Anopheles, and Culex genera. From 1,039 contigs of viral origin, we identified 229 viral species infecting mosquitoes, with the orders Picornavirales, Nodamuvirales and Sobelivirales being the most prevalent and abundant. The difference in virome composition was primarily driven by mosquito host species rather than specific collection sites or trap height.ResultsDespite environmental disparities, the virome remained remarkably uniform across different areas of the zoo, emphasizing the strong association between mosquito species and their viral communities. Furthermore, we identified a core virome shared among mosquito species, highlighting potential cross-species transmission events and underscoring the need for targeted surveillance and control measures.ConclusionThese results contribute to our understanding of the interplay between mosquitoes, the environment, and viruses, providing valuable insights for disease intervention strategies in mosquito-borne diseases.